EXPLORATORY FACTOR ANALYSIS OF TEAM CLIMATE INVENTORY (TCI) ON TECHNOLOGY START-UP - Tony Antonio; Amanda Teonata; Trianggoro Wiradinata; Adi Suryaputra; Agoes Tinus Lis Indrianto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Team climate in organization is an important element to make the innovation process in an organization works. Study on team and its behaviour is done extensively around the world. It shows the importance of a team. Team climate is one of the characteristics of an innovative team. Team Climate Inventory is a measurement scale to examine the climate factors in a team. Earlier TCI was developed by West in 1990 and then extended in 1995 and 1998. Kivinaki and Eloainio made a shorter version of West’s which consists only 14 items. The shorter version is administered to a total five teams of co-working space start-up. The technology start-up has an intensive program every day within a month under a supervision of tutor from international wellknown company and an entrepreneurial-based university. The quantitative survey was followed by interviewing some of the member and leaders of the start-ups. The item analysis shows that all items are accepted with CITC value are above 0.3. And high reliability with Cronbach’s alpha value is above 0.8. The analysis shows that TCI has 3 factors, which consist of vision, participatory safety, and support for innovation. Keywords: Team Climate, Innovation, Technology start-up